Fe-MOF derivative / charcoal nano composite material as well as preparation method and application thereof

By preparing the Fe-MOF derivative/biological carbon nano-composite material, the use of its nuclear shell structure to increase the active site exposure, solve the problem of difficulty removing water tetracycline pollution of traditional methods, and achieve efficient degradation and good stability and reusable usefulness. sex.

CN119346146APending Publication Date: 2025-01-24JIAMUSI UNIVERSITY
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411479232.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

Smart Images

  • Figure CN119346146A_ABST
    Figure CN119346146A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe-MOF derivative / biochar nano composite material as well as a preparation method and application thereof, and belongs to the field of degradation of organic pollutants in a water body. The invention aims to solve the problems of unstable structure, easy agglomeration and the like at high temperature. The preparation method comprises the following steps: by taking an Fe-MOF derivative as a precursor and charcoal as a carrier material, carrying out in-situ synthesis on Fe-MOF, and carrying out high-temperature calcination on the surface of charcoal (BC). The metal carbon-based composite material prepared by the method shows excellent catalytic performance in catalytic degradation of tetracycline in a water body. Meanwhile, the prepared multiphase composite catalytic material has good stability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of degradation of organic pollutants in water bodies, and specifically relates to a Fe-MOF derivative / biochar nanocomposite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industrialization and urbanization, environmental pollution has become a global challenge. The residues of tetracycline in water bodies have become an important problem of environmental pollution. The residues of tetracycline in the environment mainly come from agricultural and pharmaceutical wastes. They enter water bodies and soil through wastewater discharge, livestock farm feces and the application of antibiotics to crops, which not only destroy aquatic ecosystems, but also may enter the human body through drinking water and the food chain, affecting human health. Due to its stable structure and non-biodegradable nature, traditional treatment methods such as adsorption, biodegradation and membrane separation are difficult to completely remove tetracycline. Therefore, it is necessary to adopt efficient and rapid methods to degrade it in order to protect the ecosystem and human health.

[0003] In the process of degrading water pollutants, many oxidants can degrade pollutants, but due to their long reaction cycle and insignificant effect, they cannot be widely used in medicine, industry, and life. Using catalysts to degrade pollutants in water can make up for the shortcomings of oxidants. Although homogeneous catalysts have high degradation activity, they are difficult to separate from the reaction system, easily cause secondary pollution of the environment, and have low recycling and reuse rates. These shortcomings greatly limit their scope of application. Developing heterogeneous catalysts with high catalytic performance and reusability is an effective way to solve this problem.

[0004] In recent years, metal organic framework materials (MOFs) have attracted worldwide attention due to their adjustable pores and good chemical compatibility, especially in the field of water pollution treatment. Compared with MOFs materials, MOF derivatives have better catalytic effects due to their many reactive sites and large specific area. However, they are structurally unstable at high temperatures and are prone to agglomeration. Summary of the invention

[0005] The present invention uses Fe-MOF derivatives as precursors and biochar as carrier materials to prepare a Fe-MOF derivative / biochar nanocomposite material. Due to its unique core-shell structure (spherical Fe / Fe3C is evenly dispersed on the pore-rich BC surface, and the Fe element is mainly distributed in the core of the core-shell structure), more metal active sites can be exposed, the contact area between the substrate and the active sites is increased, the catalytic activity of the composite material is improved, and excellent degradation performance is shown in the tetracycline degradation experiment.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The object of the present invention is to provide a method for preparing a Fe-MOF derivative / biochar nanocomposite material, comprising the following steps:

[0008] Step 1: Powdering peanut shells, and then calcining them under an inert gas atmosphere to obtain biochar;

[0009] Step 2: Add ferric nitrate nonahydrate, terephthalic acid and the biochar obtained in step 1 to N,N-dimethylformamide in sequence, stir until uniform, heat at a certain temperature for a certain time, cool to room temperature, filter, wash with anhydrous ethanol and water alternately, and dry.

[0010] Step 3: Then, under the protection of an inert gas atmosphere, the temperature is raised to 600°C-1000°C (preferably 800°C), kept warm for a certain period of time, and annealed to room temperature to obtain a Fe-MOF derivative / biochar nanocomposite material (core-shell Fe / Fe3C@C).

[0011] It is further defined that in step 1, the peanut shells are made into powder according to the following operation: the peanut shells are washed with pure water for at least three times, then dried at 60° C.-80° C. for at least 12 hours, crushed and sieved.

[0012] Further, in step 1, the temperature is raised to 800°C at a rate of 5°C / min, and the calcination is continued for 120 min.

[0013] It is further defined that in step 2, the volume ratio of the mass of ferric nitrate nonahydrate, the mass of terephthalic acid, the mass of biochar and N,N-dimethylformamide is 100 mg: 75 mg: (0.3-2) g: 70 mL.

[0014] It is further defined that in step 2, the volume ratio of the mass of ferric nitrate nonahydrate, the mass of terephthalic acid, the mass of biochar and N,N-dimethylformamide is 100 mg: 75 mg: 0.5 g: 70 mL.

[0015] It is further defined that in step 2, the stirring speed is 5000 r / min; and heating is performed at 160° C. to 180° C. for at least 6 hours.

[0016] It is further defined that in step three, the temperature is increased at a rate of 5°C / min to 10°C / min.

[0017] It is further defined that in step three, the temperature is kept warm for 2 to 4 hours.

[0018] The Fe-MOF derivative / biochar nanocomposite material prepared by any of the above methods has a core-shell structure, spherical Fe / is uniformly dispersed on the pore-rich BC surface, and the Fe element is mainly distributed in the core of the core-shell structure.

[0019] In addition, the Fe-MOF derivative / biochar nanocomposite material of the present invention is used for catalytic degradation of organic pollutants in water. Preferably, the organic pollutant is tetracycline; the degradation rate of tetracycline by the core-shell Fe / Fe3C@C-0.5 composite material can reach 99.55%.

[0020] The present invention adopts metal organic framework (Fe-MOF) and biochar to prepare metal nanocomposite materials. Since Fe-MOF is combined with porous biochar, during thermal polymerization, it can effectively prevent iron-iron bonding, so that iron atoms will not gather together, and the metallic iron has good dispersibility. Through pyrolysis, the metallic iron is in situ reduced on the surface of the carbon substrate, and the active sites are fully exposed, which can effectively contact with the reaction substrate. The metal carbon-based composite material prepared by the method of the present invention shows excellent catalytic performance in catalytic degradation of tetracycline in water. At the same time, the prepared multiphase composite catalytic material has good stability and recyclability.

[0021] The present invention prepares a catalyst Fe / Fe3C@C composite material by in-situ synthesizing Fe-MOF and calcining it at high temperature on the surface of biochar (BC). The Fe / Fe3C@C composite material has the following advantages as a catalyst:

[0022] (1) BC as a carrier material can not only effectively inhibit the agglomeration of metal particles, but also improve the electron transfer performance of the composite material.

[0023] (2) The core-shell Fe / Fe3C@C nanoparticles are evenly distributed on the BC surface, increasing the contact area between the active sites and the substrate, thereby improving the catalytic efficiency.

[0024] (3) Free radicals (O2 ·- , OH and SO4 ·- ) and non-free radicals ( 1 O2), and its dual degradation channels are more conducive to the removal of TC in water. Based on the above characteristics of Fe / Fe3C@C materials, the composite catalyst has good catalytic performance for the degradation of TC and has obvious practical application potential. The present invention provides a new method for designing and synthesizing efficient catalytic compounds.

[0025] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1SEM images of (a) Fe-MOFs, (b) Fe-MOFs / C, (c) Fe@C, and (d) Fe / Fe3C@C-0.5; (e) TEM and (f) HRTEM images of Fe / Fe3C@C and (gk) corresponding EDS mapping;

[0027] Figure 2 (a) and (b) are the N2 adsorption and desorption curves and pore size distribution curves of Fe / Fe3C@C-0.3, Fe / Fe3C@C-0.5 and Fe / Fe3C@C-1, respectively;

[0028] Figure 3 This is the UV-visible spectrum of TC degradation in the Fe / Fe3C@C-0.5+PDS system. ([Carbon content in catalyst] = 0.5 g, catalyst calcination temperature = 800 °C, [catalyst dosage] = 0.02 g L -1 , [sodium persulfate] = 0.1 gL -1 , [TC] = 20 mgL -1 , [volume of solution] = 100 mL, pH = 7, T = 318 K. )

[0029] Figure 4 (a) Reusability of Fe / Fe3C@C-0.5 for TC degradation in Fe / Fe3C@C-0.5 / PDS system; (b) High-resolution Fe 2p spectrum of Fe / Fe3C@C before and after degradation reaction; (c) Fe Moosbauer spectrum of Fe / Fe / Fe3C@C before and after degradation reaction; (d) Hysteresis curve of Fe / Fe3C@C-(0.3,0.5,1);

[0030] Figure 5 The effect of different calcination temperature systems on TC degradation. ([Carbon content in catalyst] = 0.5 g, [catalyst dosage] = 0.03 g L -1 , [sodium persulfate] = 0.06 gL-1, [TC] = 10 mgL -1 , [solution volume] = 100 mL, T = 298 K, pH = 7. ) DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0032] Example 1: The preparation method of the Fe-MOF derivative / biochar nanocomposite material in this example is carried out according to the following steps:

[0033] Preparation of biochar (BC)

[0034] The peanut shells were washed three times with pure water, placed in a drying oven, dried at 60° C. for 12 hours, crushed, and passed through a 100-mesh sieve to obtain dry powder.

[0035] 1.0 g of the dried powder was placed in a porcelain boat, placed in a tube furnace, and high-purity nitrogen was continuously introduced at a rate of 10 ml / min for 30 minutes, then the temperature was raised to 800°C at a rate of 5°C / min, and the calcination was continued for 120 minutes, and then annealed to room temperature. The obtained product was stored in a desiccator away from light.

[0036] Preparation of Fe-MOF / C and its derivatives

[0037] 100 mg of ferric nitrate nonahydrate (Fe(NO3)·9H2O), 75 mg of terephthalic acid (TPA) and 0.5 g of biochar were placed in 70 mL of N,N-dimethylformamide (DMF) solution and stirred at 5000 r / min for 10 min. The mixture was then transferred to a 100 mL polytetrafluoroethylene-lined autoclave, heated at 180 °C for 6 hours, cooled to room temperature, and the obtained product was filtered to obtain a solid powder, which was washed alternately with ethanol and water for 3 times, and dried at 60 °C for 12 h to obtain a gray powder named Fe-MOF / C-0.5. The obtained solid powder was placed in a porcelain boat, placed in a tube furnace, and high-purity nitrogen was introduced at 10 ml / min for 30 minutes. The temperature was raised to 800 °C at a rate of 5 °C / min, kept at this temperature for 120 min, and then annealed to room temperature to obtain a black powder named core-shell Fe / Fe3C@C-0.5.

[0038] The preparation methods of Fe-MOF / C-0.3, Fe-MOF / C-1, Fe-MOF / C-2 and Fe-MOF / C-0.5 are the same, except that 0.3g, 1g and 2g of biochar are added to the precursor solution for synthesizing Fe-MOF, respectively. Fe-MOF / C-0.3, Fe-MOF / C-1, Fe-MOF / C-2 and Fe-MOF / C-0.5 are calcined by the same method as above to obtain Fe / Fe3C@C-0.3, Fe / Fe3C@C-0.5, Fe / Fe3C@C-1 and Fe / Fe3C@C-2, respectively.

[0039] The main Fe species in Fe / Fe3C@C are Fe3C and Fe 0 .

[0040] The ID / IG values ​​of Fe / Fe3C@C-0.3, Fe / Fe3C@C-0.5 and Fe / Fe3C@-1 are 0.71, 0.53 and 0.66, respectively, indicating that the degree of graphitization of Fe / Fe3C@C-1 and Fe / Fe3C@C-0.3 is better than that of Fe / Fe3C@C-0.5.

[0041] Catalyst Fe / Fe3C@C at 2900cm -1 ~3700cm -1 The broad peaks at 1514 cm-1 belong to the -OH stretching vibration band. Compared with Fe / Fe3C@C-0.3 and Fe / Fe3C@C-1, the peak intensity of Fe / Fe3C@C-0.5 is relatively high, indicating the presence of more hydroxyl functional groups. -1 ~1694cm -1 At 900cm, it corresponds to the stretching vibration bands of C=O and C=C. -1 ~1500cm -1 The peaks at correspond to the CO and CC stretching vibration bands.

[0042] Comparative Example: Preparation of Fe-MOF and its derivatives

[0043] Fe-MOF was prepared by the method reported in the literature. 100 mg of ferric nitrate nonahydrate (Fe(NO3)·9H2O) and 75 mg of terephthalic acid (TPA) were dissolved in 70 mL of N,N-dimethylformamide (DMF) solution and stirred at 5000 r / min for 10 min. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined autoclave, heated at 180 ° C for 6 hours, cooled to room temperature, and the obtained product was filtered to obtain a solid powder, which was washed alternately with ethanol and water for 3 times, and dried at 60 ° C for 12 hours to obtain an orange powder. 1.0 g of the obtained solid powder was placed in a porcelain boat and placed in a tube furnace. After continuous high-purity nitrogen was introduced for 30 minutes, the temperature was raised to 800 ° C at a rate of 5 ° C / min, kept constant for 120 minutes, and then annealed to room temperature. The black substance Fe@C was obtained.

[0044] According to the scanning electron microscope (SEM) images, Figure 1 As shown in (a), Fe-MOF shows a regular cylindrical bipyramidal geometry. After loading onto BC, the morphology and size of Fe-MOF do not change significantly, as shown in Figure 1 (b) If Figure 1 (c) After calcination at 800 °C, Fe-MOF becomes spherical Fe / Fe3C. Figure 1 (d), Fe / Fe3C is uniformly dispersed on the porous BC surface, which can effectively increase the contact area between pollutants and catalysts. In order to further confirm its structure and morphology, transmission electron microscopy (TEM) images of Fe / Fe3C@C-0.5 samples were detected. Figure 1As shown in (e), the particle diameter of Fe / Fe3C@C-0.5 is about 200nm. Under high-resolution transmission electron microscopy (HRTEM), Figure 1 In (f), lattice fringes of 0.34 nm, 0.143 nm, and 0.203 nm can be clearly observed, which are consistent with the lattice fringes spacing of BC (002), metallic Fe (200), and Fe3C (220). In addition, the EDS-mapping image confirms that the Fe element is mainly distributed in the core of the core-shell structure, and the other elements in Fe / Fe3C@C-0.5 are almost uniformly distributed throughout the structure.

[0045] The specific surface area and pore structure of Fe / Fe3C@C-0.5 were studied by nitrogen adsorption and desorption isotherms. Figure 2 As shown in Figure 1, the specific surface area of ​​the core-shell Fe / Fe3C@C-0.5 obtained by the method of Example 1 can reach 173.9 m 2 / g, significantly higher than Fe / Fe3C@C-0.3(126.3m 2 / g) and Fe / Fe3C@C-1(140.6m 2 / g), indicating that Fe / Fe3C@C-0.5 can provide more active sites. The pore size is mainly in the range of 3-8nm.

[0046] The UV-visible spectrum of TC degradation within 30 min is as follows: Figure 3 As shown, the absorption spectrum of TC exhibits two characteristic regions at 272nm and 357nm, which is the result of the different benzene ring structures of TC. As the reaction proceeds, the two main absorption peaks decrease rapidly and blue shift occurs. This is due to the erosion and breakage of the hydroxyl and amide groups on the aromatic ring B and the hydroxyl groups on the aromatic ring A by oxidizing substances. The results also show that no new peaks appear in the spectrum, indicating that TC can be quickly converted into small molecule products. High performance liquid chromatography-tandem mass spectrometry (HPLC-MS) analysis showed the presence of 13 significant degradation intermediates, with the main mass peaks appearing at =318 (P1), 301 (P2), 274 (P3), 477 (P4), 460 (P5), 344 (P6), 427 (P7), 415 (P8), 459 (P9), 130 (P10), 261 (P11), 159 (P12) and 149 (P13). There are four possible degradation pathways for TC in the present invention, including free radicals (O2 ·- , OH and SO4 ·- ) and non-free radicals ( 1 O2) pathway. TC molecules and active substances (O2 ·- , OH, SO4 ·- and 1O2) interaction, and then TC is further converted to a low-mass intermediate. In the first pathway, P1 (m / z = 318) is obtained by demethylation. Then, P2 (m / z = 301) is generated by dehydroxylation of P1 (m / z = 318), and then P3 (m / z = 274) is generated by losing the carboxyl group. The second possible pathway is that TC is first 1 O2 is oxidized to P4 (m / z = 477), and then deaminated to give P5 (m / z = 460) and P6 (m / z = 344). The products of the third pathway, in the presence of free radicals (·OH and SO4 ·- ) and non-free radicals ( 1 In the presence of O2), TC also converts to P7 (m / z = 427) and P8 (m / z = 415) by losing water molecules and methyl groups in the early degradation process. The fourth pathway is P9 (m / z = 459) and keto groups, which convert to P7 (m / z = 427) and P8 (m / z = 415) by losing water molecules and methyl groups in the early degradation process. ·- In addition, the above intermediates are gradually converted into some smaller molecules, including P10 (m / z = 130), P11 (m / z = 261), P12 (m / z = 159), and P13 (m / z = 149). Ultimately, these molecules will be mineralized into harmless carbon dioxide, water, and other inorganic ions.

[0047] When the PDS dosage is 20 mg / L, a significant degradation effect can be achieved. When the PDS dosage increases to 40 mg / L, the removal rate of the system drops to 93.3%. When the PDS dosage is 20 mg / L, the catalytic effect reaches 98.6%.

[0048] When the initial concentration of TC increased from 10 mg / L, 20 mg / L, 30 mg / L to 40 mg / L, the degradation rates of TC were 98.6%, 99.1%, 82.1% and 78.7%, respectively. This result may be that the increase in the initial TC concentration led to an increase in the number of adsorbed TCs, and many intermediates were degraded on the surface of the catalyst, limiting the oxidation reaction. Therefore, in the Fe / Fe3C@C activated persulfate system, when the tetracycline concentration continued to rise to 40 mg / L, the degradation rate gradually slowed down.

[0049] The effects of different Fe / Fe3C@C-0.5 concentration systems on TC degradation are shown in Figure 5 ,Depend on Figure 5It can be seen that the removal effect of TC in Fe / Fe3C@C-0.5 ranges from 0.01g / L to 0.04g / L. The removal rates are 81.3%, 96.8%, 80.8% and 90.6%, respectively. When the amount of catalyst increases from 0.01g / L to 0.02g / L, the contact area between the oxidant and the catalyst increases, which can provide more active sites for the catalytic reaction, accelerate the adsorption and decomposition of the oxidant on the catalyst surface, and thus produce more free radicals and non-free radicals. When the catalyst dosage exceeds 0.02g / L, the degradation effect of the system is slightly weakened. The reason may be that some catalyst nanoparticles in the system agglomerate, reducing the number of effective active sites and reducing the number of free radicals and non-free radicals.

[0050] Fe / Fe3C@C-0.5 not only has excellent degradation performance, but also has good reusability, which is an extremely important advantage in practical applications. Figure 4 As shown in (a), in the Fe / Fe3C@C-0.5 / PDS system, after 4 cycles, the TC removal efficiency dropped from 99.55% to 58.2%. The high-resolution spectrum of Fe 2p after 4 cycles was compared with the previous one, and the results showed that the Fe 0 The content of Figure 4 (b) From the Mössbauer spectrum after 4 cycles, Figure 4 (c), Fe 0 The single diffraction peak of Fe 0 The content decreased, which is consistent with the XPS results. In addition, the ICP analysis results showed that the iron content decreased slightly from 19.7783% to 17.8421%, which is consistent with the above results. Figure 4 (d) shows the hysteresis loop of Fe / Fe3C@C-0.5 obtained at 25 °C. Fe / Fe3C@C-0.5 exhibits strong paramagnetism at room temperature. Under the action of an external magnetic field, the Fe / Fe3C@C-0.5 particles can be easily separated from the treated water, allowing the material to be recycled and reused. The reasons for the decrease in removal efficiency after 4 cycles are as follows: (1) The adsorption of TC or residual intermediates on the surface of Fe / Fe3C@C-0.5 blocks some active sites and inhibits the partial reactivity of Fe / Fe3C@C-0.5 towards PDS; (2) During the multiple washing and drying processes after the reaction, Fe and Fe3C are slightly leached from the Fe / Fe3C@C-0.5 catalyst, resulting in the loss of active substances; (3) Fe 0 Participate in the formation of free radicals, leading to Fe 0The content is reduced. In summary, the generated ROS can degrade tetracycline into water and carbon dioxide. The results of the recycling experiment show that the Fe / Fe3C@C-0.5 composite material has good structural stability and reusability during the application process.

[0051] Fe / Fe3C@C-600, Fe / Fe3C@C-800 and Fe / Fe3C@C-1000 were added to the catalytic system. Figure 5 , the removal efficiencies of TC within 30 min were 52.8% and 74.2%, respectively, and the removal efficiency of Fe / Fe3C@C-800 was as high as 89.8%. The calcination conditions of the prepared samples were all set at 800 °C.

[0052] By calcining Fe-MOF / BC precursor at high temperature, Fe / Fe3C@Cx composite materials with uniform dispersion of Fe / Fe3C nanoparticles were successfully prepared, where x was 0.3, 0.5, 1 or 2, and had good degradation activity in the removal of TC. Using BC as a carrier can not only effectively inhibit the agglomeration of metal nanoparticles, but also improve the electron transfer performance of the composite material. In addition, the degradation efficiency of TC is significant, and the degradation rate of the core-shell Fe / Fe3C@C-0.5 composite material reaches 99.55%, which has great practical application potential. From the study of its mechanism, the efficient removal of TC can be attributed to the simultaneous existence of two degradation pathways: free radical pathway and non-free radical pathway. The results show that the Fe / Fe3C@C composite material can be used to degrade various organic pollutants.

Claims

1. A method for preparing a Fe-MOF derivative / biochar nanocomposite material, characterized in that: The following steps are involved: Step 1: Powdering peanut shells, and then calcining them under an inert gas atmosphere to obtain biochar; Step 2: Add ferric nitrate nonahydrate, terephthalic acid and the biochar obtained in step 1 to N,N-dimethylformamide in sequence, stir until uniform, heat at a certain temperature for a certain time, cool to room temperature, filter, wash with anhydrous ethanol and water alternately, and dry. Step 3: Then, under the protection of an inert gas atmosphere, the temperature is raised to 600° C.-1000° C., kept warm for a certain period of time, and annealed to room temperature to obtain a Fe-MOF derivative / biochar nanocomposite material.

2. The method according to claim 1, characterized in that: In step 1, the peanut shells are made into powder according to the following operation: the peanut shells are washed with purified water for at least three times, then dried at 60° C.-80° C. for at least 12 hours, crushed and sieved.

3. The method according to claim 1, characterized in that: In step 1, the temperature was raised to 800°C at a rate of 5°C / min and calcination was continued for 120 min.

4. The method according to claim 1, characterized in that: In step 2, the volume ratio of the mass of ferric nitrate nonahydrate, the mass of terephthalic acid, the mass of biochar and N,N-dimethylformamide is 100 mg: 75 mg: (0.3-2) g: 70 mL.

5. The method according to claim 1, characterized in that: In step 2, the volume ratio of the mass of ferric nitrate nonahydrate, the mass of terephthalic acid, the mass of biochar and N,N-dimethylformamide is 100 mg: 75 mg: 0.5 g: 70 mL.

6. The method according to claim 1, characterized in that: In step 2, the stirring speed is 5000 r / min; heating is performed at 160° C. to 180° C. for at least 6 hours.

7. The method according to claim 1, characterized in that: In step 3, the temperature is increased at a rate of 5°C / min to 10°C / min.

8. The method according to claim 1, characterized in that: In step 3, keep warm for 2h to 4h.

9. A Fe-MOF derivative / biochar nanocomposite material prepared by the method according to any one of claims 1 to 8, characterized in that: The composite material is in a core-shell structure.

10. The Fe-MOF derivative / biochar nanocomposite prepared by the method according to any one of claims 1 to 8 or the Fe-MOF derivative / biochar nanocomposite according to claim 9 is used for catalytic degradation of tetracycline in water.

Citation Information

Cited By

  • MOF-based TiO2 / BC composite photocatalyst as well as preparation method and application thereof

    CN120054650A

  • Wheat straw decomposition-based returning-to-field fertilizer as well as preparation method and application thereof

    CN120117939A

  • Preparation method and application of porous core-shell iron-nitrogen-carbon catalyst

    CN121082307A

  • Method for removing antibiotics in water body based on iron-nitrogen co-doped mesoporous carbon activated peroxymonosulfate

    CN121085410A

  • Preparation and application of Fe-Fe3C nitrogen-doped porous carbon composite material loaded with BiOBr nanosheet

    CN121715205A